STUDI KUALITATIF: PERSEPSI REMAJA PENDERITA KANKER TERHADAP PELAYANAN KEPERAWATAN - Dirayati Sharfina; Indria L. Gamayanti; Fitri Haryanti; Yulis Hati (Jurnal Ilmiah Kebidanan Imelda, 2020)
Adolescent with cancer have a complex problem. Adolescents with cancer at risk for developmental phase delay caused limitations in carrying out its role as adolescents, because of the side effects of medication and intensive relationships with health care providers. Nurses are health workers who have a frequency of more interaction to the teenagers who suffer from cancer. Form of nursing care provided by nurse will shape perceptions of teenagers. Adolescent perception of cancer patients with the care received does not match the hope will establish a nursing care desired by adolescents. This study to explore perception and hope of adolescents toward quality of nursing care in Adam Malik Hospital Medan. Qualitative research methods through a phenomenological approach. Adolescent with cancer as research subjects, aged 13-19 years who had been diagnosed with cancer and was undergoing treatment protocol. The sampling technique used the maximum variance. Data were collected through semi-structured interviews with tools interview, observation, field notes, and tools as well as the record will be analyzed by the method Colaizzi The themes that reflect the perceptions and hope of adolescents to nursing care include 1) an overview of nurses’ profile, 2) the ability and skills of nurses, 3) nurses’ attitude, 4) preparedness nurses, 5) the provision of social support. Adolescents also hope hospital’s management add room facilities in order to easy to access the health service especially service care for adolescents. Adolescents with cancer have a different impression at the beginning of the meeting and after getting care by nurses. Further researcher can choose suitable location to interview and research about hope of adolescent’s cancer and nurse’s role in adolescent’s cancer.